2017
DOI: 10.5021/ad.2017.29.3.327
|View full text |Cite
|
Sign up to set email alerts
|

Acral Lentiginous Melanoma, Indolent Subtype Diagnosed by En Bloc Excision: A Case Report

Abstract: Nail unit melanoma is a type of acral lentiginous melanoma and requires histopathologic examination for a confirmed diagnosis. However, inadequate biopsy techniques make definitive diagnosis difficult. A 61-year-old man presented with progressive nail pigmentation for 15 years, which was clinically highly suspicious for malignancy. Acral lentiginous melanoma was not detected in punch and longitudinal biopsy specimens, but en bloc excision tissue revealed melanoma. Acral lentiginous melanoma is known to have a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…34,35 Moreover, indolent acral melanoma with long radial growth phase has been reported in Asian populations, and we found many similar cases of acral melanoma presenting longer horizontal diameter than tumor thickness in our cohort. 18,19 These observations may contribute to explaining the lack of significant difference in Breslow thickness between acral and nonacral melanoma in this study.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…34,35 Moreover, indolent acral melanoma with long radial growth phase has been reported in Asian populations, and we found many similar cases of acral melanoma presenting longer horizontal diameter than tumor thickness in our cohort. 18,19 These observations may contribute to explaining the lack of significant difference in Breslow thickness between acral and nonacral melanoma in this study.…”
Section: Discussionmentioning
confidence: 62%
“…18 Huge acral melanoma with a clinical diameter measuring 4-6 cm without dermal invasion has been described. 18,19 A peculiar spreading pattern has been observed in acral melanoma which may be associated with predisposing factors, anatomical structures and genetic predisposition that differ from non-acral melanoma. 20,21 We performed this study to elucidate whether there is any difference in progression pattern between acral and nonacral melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…Aggressive tumor behavior, 7,19,20 poor biopsy technique or failure to biopsy in the earliest disease stages, 7,11,[21][22][23][24][25][26][27][28][29] Because risks factors for SUM are unknown, early detection is the currently only way to potentially improve survival and functionality in these patients. 24,35,36 The incidence of SUM increased 2.04% annually 2012 to 2016, with the nail biopsy rate increasing at a faster rate, except for those performed by dermatologists (8.62% decrease).…”
Section: Discussionmentioning
confidence: 99%
“…2). 20,24 In ambiguous cases, fluorescence in situ hybridization (FISH) can provide additional information. A study analyzing seven cases of NM by FISH showed that NM commonly presented 6p25 (RREB1) gain (100%), 11q13 (CCND1) gain (86%), and both 6q23 (MYB) loss and 8q24.1 (MYC) gain (71%).…”
Section: Histopathology Findingsmentioning
confidence: 99%